2014
DOI: 10.5551/jat.19877
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Autonomic Nervous System and the Second Derivative of the Finger Photoplethysmogram Indices

Abstract: A multivariate regression analysis showed that the LF, HF and heart rate were independent determinants of the c/a. Furthermore, the c/a values were significantly lower in the patients with hypertension, diabetes mellitus and hyperlipidemia than in those without these diseases, and a reduced c/a was significantly associated with increased serum triglyceride and total cholesterol concentrations. Conclusions: These findings suggest that a decrease in c/a is associated with a reduced baroreflex response of the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…To resolve this issue, more physiological parameters that are relevant to arterial properties rather than PTT should be introduced to estimate BP in individuals with heart disease. For instance, useful features of the second derivative of PPG (SDPPG) could be potent candidates (Baek et al 2010), because the indices of SDPPG denote stiffness of large arteries, peripheral vascular resistance and vascular aging (Kohjitani et al 2014). Figure 6 shows the representative PPG waveform of one healthy subject and a patient diagnosed with congestive heart failure, in which the ratios of the absolute of the height of the 'b' wave and that of the 'd' wave to that of 'a' wave, namely the b:a and d:a ratios, could evaluate the arterial properties (Hashimoto et al 2002).…”
Section: Influence Of Heart Disease On Ptt-based Bp Estimationmentioning
confidence: 99%
“…To resolve this issue, more physiological parameters that are relevant to arterial properties rather than PTT should be introduced to estimate BP in individuals with heart disease. For instance, useful features of the second derivative of PPG (SDPPG) could be potent candidates (Baek et al 2010), because the indices of SDPPG denote stiffness of large arteries, peripheral vascular resistance and vascular aging (Kohjitani et al 2014). Figure 6 shows the representative PPG waveform of one healthy subject and a patient diagnosed with congestive heart failure, in which the ratios of the absolute of the height of the 'b' wave and that of the 'd' wave to that of 'a' wave, namely the b:a and d:a ratios, could evaluate the arterial properties (Hashimoto et al 2002).…”
Section: Influence Of Heart Disease On Ptt-based Bp Estimationmentioning
confidence: 99%
“…It is commonly known as a parameter for assessing arteriosclerosis, which is representative of severe functional arterial aging. Several previous studies have also reported that patients with any history of arteriosclerotic diseases, including hypertension, diabetes mellitus, and hypercholesterolemia, had higher SDPTG-AI values [2,7,27].…”
Section: Discussionmentioning
confidence: 85%
“…During exercise, both c/a and d/a were not detectable in either group. It has been reported that a reduced c/a was associated with a decreased baroreflex responses and with a reduced cardiac parasympathetic tone (Kohjitani et al, 2014 ). Moreover, the c/a was related to hypertension, diabetes mellitus and hyperlipidemia as well as elevated total cholesterol concentrations (Kohjitani et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a reduced c/a was associated with a decreased baroreflex responses and with a reduced cardiac parasympathetic tone (Kohjitani et al, 2014 ). Moreover, the c/a was related to hypertension, diabetes mellitus and hyperlipidemia as well as elevated total cholesterol concentrations (Kohjitani et al, 2014 ). In addition, some studies have reported that a decline in these parameters was associated with increased arterial stiffness or age (Rivas-Vilchis et al, 2007 ; Rozi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%